2015
DOI: 10.1007/s13258-015-0307-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of β-amyrin synthase gene in Bupleurum chinense

Abstract: Bupleurum chinense DC. is one of the source plants of a well-known crude drug, Chai hu (Radix Bupleuri), producing triterpenoid saponins (saikosaponins) with a wide-spectrum of pharmacological applications. The biosynthesis of triterpenoid saponins involved with the cyclizing of the precursor 2,3-oxidosqualene to produce the first committed triterpene b-amyrin catalyzed by b-amyrin synthase (b-AS), whereafter diverse of triterpenoid saponins was biosynthesized. In addition, 2,3-oxidosqualene could be catalyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A previous study indicated that β-AS in B. kaoi and B. chinense exhibits tissue-specific responses to both MeJA and PEG (Lin et al, 2013;Zhang et al, 2016). We have also cloned the promoter of β-AS in B. chinense and evaluated its activity previously (Gao et al, 2015). We found three β-AS genes (BcBAMS98705, BcBAMS12370, and BcBAMS21523) with significantly increased expression in S3 of B. chinense.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that β-AS in B. kaoi and B. chinense exhibits tissue-specific responses to both MeJA and PEG (Lin et al, 2013;Zhang et al, 2016). We have also cloned the promoter of β-AS in B. chinense and evaluated its activity previously (Gao et al, 2015). We found three β-AS genes (BcBAMS98705, BcBAMS12370, and BcBAMS21523) with significantly increased expression in S3 of B. chinense.…”
Section: Discussionmentioning
confidence: 99%
“…β-AS is a member of the OSC (oxidosqualene cyclase) family, which acts in the initial step of the biosynthesis of SSs, and the resultant β-amyrin is the backbone of various SS monomers [ 49 ]. β-AS was an important branch point between specialized and primary metabolism and could regulate the metabolic accumulation of triterpenoid saponins.…”
Section: Discussionmentioning
confidence: 99%
“…DDSs are uncommon in nature, which result in the unique ginsenoside scaffolds predominant in Panax species, and β -ASs are widespread in plant kingdom such as in Araliaceae 113 , Umbelliferae 114 , Leguminosae 115 and other families 116 , 117 . DDS and β -AS from Panax genus are single product producing enzymes, while some other OSCs are multifunctional enzymes.…”
Section: Biosynthetic Pathways Of Ginsenosidesmentioning
confidence: 99%